INTER-PERSONAL RELATIONS IN THE EDUCATIONAL PROCESS - Umarova Malika Khisabiddinovna; Ibragimova Dilobar Ahmad qizi (European Journal of Humanities and Educational Advancements, 2021)
It is well known that in the educational process, any pedagogical technology is based on the principles of education, which represent a new project of the educational process, and is focused on the individual student. Therefore, the interaction and communication between teacher and students, their interaction with each other, should serve to form human qualities in students. In the process of such a friendly relationship, students develop the skills to work in interpersonal relationships. This article focuses on the nature of interpersonal relationships